Case report: morphological challenges to surgical repair in complete atrioventricular septal defect with isolated ventricular component - Larsson, Martina; Synnergren, Mats; Rodrigo, Thushara (Cardiology in the young, 2025)
We describe a trisomy 21 patient with postnatal diagnosis of atrioventricular septal defect with isolated ventricular component who had a complicated post-surgical course following complete repair. Clinical outcomes included moderate-severe residual atrioventricular valve regurgitation needing re-operation, complete heart block leading to pacemaker insertion, seizures secondary to subdural haemorrhages, and chylothorax. We describe the surgical considerations specific to this cardiac morphology.